Presumption of Innocence and Testimonial Evidence. Some Considerations from Canon Criminal Law and the Psychology of Testimony - Campos Martínez, Francisco José (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2025)
Some canonical crimes, particularly those committed in private, rely on the victim’s testimony as their primary, and often sole, evidence. Therefore, its acquisition and assessment is a matter of particular complexity and sensitivity, as it must combine the good of potential victims with the presumption of innocence of the accused. This article presents some of the requirements and limits that the principle of the presumption of innocence imposes as a rule of evidence in criminal cases and offers, from the perspective of secular and canonical criminal law and the psychology of testimony, some considerations that can help researchers and investigators to improve and implement practices and criteria for action consistent with the presumption of innocence in obtaining, interpreting, and assessing the evidential value of testimony.
Keywords: presumption of innocence; testimonial evidence; canonical crimes; sexual abuse; credibility of testimony; evidential value; canonical criminal process; psychology of testimony